Carbon Accounting for Compost Use in Urban Areas. Issue 4 (2nd October 2019) - Brown, Sally; Beecher, Ned
Abstract: Developing biosolids-based composts or soil blends suitable for use in urban areas is increasingly common. End uses for compost vary and can include use as a soil conditioner for existing turf, to establish new turf, for tree planting, in urban agriculture, and for use along highway right-of-ways. The carbon benefits/costs of biosolids compost were modeled for King County, Washington. Soil carbon sequestration was highest for use on disturbed soils such as new housing developments, neglected urban soils, or highway right-of-ways (–1.1 Mg CO2eq per Mg compost) and lowest for use in well-tended yards or other highly maintained landscapes (–0.036 Mg CO2eq per Mg compost). Compost use for tree growth, calculated over a 30-year period, added above-ground sequestration benefits ranging from –1.53 Mg CO2eq per Mg compost for a mature tree grown on a healthy soil to –4.58 Mg CO2eq per Mg compost for a newly planted tree grown on a disturbed site. Assuming a 20 km haul distance, transport costs ranged from 0.005 Mg CO2eq per Mg compost for delivery in a 5 Mg truck to 0.09 Mg CO2eq per Mg compost for pick up in a personal vehicle. Ecosystem services associated with different end uses for compost in urban areas also vary. This model suggests that while uses for biosolids compost will likely be varied, for a program as a whole, significant carbon benefits can be expected.